Advanced Raspberry Pi : Raspbian Linux and GPIO integration - Gay, Warren (Technology in action series., 2018)
Jump right into the pro-level guts of the Raspberry Pi with complete schematics and detailed hardware explanations as your guide. You'll tinker with runlevels, reporting voltages and temperatures, and work on a variety of project examples that you can tune for your own project ideas. This book is fully updated for the latest Pi boards with three chapters dedicated to GPIO to help you master key aspects of the Raspberry Pi. You'll work with Linux driver information and explore the different Raspberry Pi models, including the Pi Zero, Pi Zero W, Pi 2, Pi3 B and Pi3 B+. You'll also review a variety of project examples that you can tune for your own project ideas. Other topics covered include the 1-Wire driver interface, how to configure a serial Linux console, and cross-compile code, including the Linux kernel. You'll find yourself turning to Advanced Raspberry Pi over and over again for both inspiration and reference. Whether you're an electronics professional, an entrepreneurial maker, or just looking for more detailed information on the Raspberry Pi, this is exactly the book for you.